Wege zu einer Ethik Neue Ansätze aus Theologie und Recht zwischen modernen Herausforderungen und islamischer Tradition - Alsoufi, Rana; Kurnaz, Serdar; Sievers, Mira (Theologie, Bildung, Ethik und Recht des Islam, 2023)
Islamic theological studies in Germany are regularly asked about the contribution of 'Islamic ethics' to the present. This raises the question of how contemporary ethical questions can be answered with respect to Islamic theological tradition. This book first presents four conceptions of ethics by scholars of different theological orientations from Islamic history. This is followed by a discussion of four contemporary examples from the field of sexual ethics, in which these approaches are made fruitful for their discussion. With contributions by Fatma Akan Ayyildiz, Bahattin Akyol, Dr. Mehrdad Alipour and Selma Schwarz.